Efficacy of Vitamin B1, B6, and B12 Forte Therapy in Peripheral Neuropathy Patients - Meyvita Silviana; Dodik Tugasworo; Maria Belladonna (Diponegoro International Medical Journal, 2021)
Background: Peripheral neuropathy can be caused by diabetes mellitus, nutritional deficiencies, entrapment or Carpal Tunnel Syndrome (CTS), and idiopathic.Objective: To determine the therapeutic efficacy of Vitamin B1, B6, and B12 forte in relieving symptoms of peripheral neuropathy.Methods: This was pre- and post-experimental study involving patients with moderate peripheral neuropathy (Toronto Clinical Neuropathy Score [TCNS] ≥6 and Michigan Neuropathy Screening Instrument [MNSI] ≥7) taken from outpatient neurological clinic of Dr. Kariadi Hospital, Semarang. The patient was prescribed Vit B1 100 mg, B6 100 mg, and B12 5000 mcg once daily for 2 months. Evaluation of the numerical pain rating scale in the form of VAS and Total Symptom Score (TSS) was conducted at the first and second month. The VAS score difference test was conducted with the Wilcoxon test and TSS with the Post Hoc test and considered significant if p <0.05.Results: There were 30 patients aged 18 - 65 years, consisted of 70% female and 30% male. The etiology of peripheral neuropathy were idiopathic (40%), CTS (26.7%), DM (23.3%), and HNP (10%). There were significant differences of the VAS scale  and TSS at every evaluations.Conclusion: Administration of VitB1, B6, and B12 forte relieved symptoms of moderate peripheral neuropathy with improvement of VAS and TSS scores